Morphology and Crystal Planes Effects on Supercapacitance of CeO2 Nanostructures: Electrochemical and Molecular Dynamics Studies. (9th August 2018) - Jeyaranjan, Aadithya; Sakthivel, Tamil Selvan; Molinari, Marco; Sayle, Dean C.; Seal, Sudipta
Abstract: Nano cerium oxide (CeO2 ) is a promising supercapacitor material, but the effect of morphology on charge storage capacity remains elusive. To determine this effect, three different morphologies, nanorods, cubes, and particles are synthesized by a one‐step hydrothermal process. Electrochemical evaluation through cyclic voltammetry and galvanostatic charge–discharge techniques reveals specific capacitance to be strongly dependent on the nanostructure morphology. The highest specific capacitance in nanorods (162.47 F g −1 ) is due to the substantially larger surface area relative to the other two morphologies and the predominant exposure of the highly reactive 110 and 100 planes. At comparable surface areas, exposed crystal planes exhibit a profound effect on charge storage. The exposure of highly reactive 100 planes in nanocubes induce a greater specific capacitance compared to nanoparticles, which are dominated by the less reactive 111 facets. The experimental findings are supported by reactivity maps of the nanostructures generated by molecular dynamics simulations. This study indicates that supercapacitors with higher charge storage can be designed through a nanostructure morphology selection strategy. Abstract : Morphology and crystal plane‐dependent supercapacitance of CeO2 nanostructures is explored using electrochemical experiments and molecular dynamics simulations. The exposed crystals planes play a crucial role in supercapacitor performance and rate capability of CeO2 nanostructures. Understanding the fundamental effect of exposed crystal planes on charge storage helps designing nanomaterials with superior supercapacitor performance.